(untitled) (Fiep Bulletin - online, 2011)
This study deals with the nature of dance in school, with a view to transformation through the practice of physical education. These various combinations of influences are present in everyday life of human beings. The dances, sports, wrestling, gymnastics and games make up a vast cultural heritage that should be valued, known and enjoyed. The objective was to encourage the creation of projects that allow body language towards the seizure of movement skills, rhythms, contact forms and symbols of their own, and the cultural experience of the human being, were organized educational activities (intervention), and the its application in the schools, with a group of 101 subjects of both sexes, in bands of 10 to 13 years, enrolled in three public schools in the city of Macapá-AP. Considering that these matters are still minimal, limited access to a limited number of people in the city, that from this research has a major contribution to make integration with other disciplines, but it also becomes necessary in preparing the program education, aimed at promoting full of essential school, encouraging the opening of new places for anyone interested in knowing, learning, and participate in the art of dance in the context of physical education.